PELAKSANAAN BIMBINGAN BERKELANJUTAN SEBAGAI UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN DI SD N BANDUNGREJO 1 PADA SEMESTER GASAL TAHUN PELAJARAN 2014/2015 - Suharningsih, Suharningsih (Universitas Negeri Semarang, 2016)
The objectives of the study was to determine whether the presence of continuous counseling implementation can improve the teachers competence in preparing a lesson plan in Bandungrejo 1 Mranggen Demak State Elementary School in odd semester, academic year 2014/2015. This research was qualitative. Therefore, it used action research approach to school. The main data obtained from informants such as school principals, and teachers. Data were collected by observation, interview, and documentation methods. The results showed that continuous counseling can improve Bandungrejo 1 Mranggen Demak State Elementary School teacher competence in preparing the Lesson Plan. The improvements can be seen qualitatively and quantitatively. Improved quality is evident from the improvement in the average value of the teachers competency in preparing lesson plans from the initial data 24.6% to 53.9% in the first cycle, and increased to 80.9% in the second cycle. An increase in quantity, which indicated the presence of teachers to prepare lesson plans with either of the preliminary data 27% increase to 63.6% in the first cycle, and increased again to 90.9% in the second cycle. Thus, there was also an improvement about 27.3% from cycle I.